Answer :

Given:


y=axn+1 +bx-n





λy=n(n+1)a xn-1+2 +n(n+1)bx-n-2+2


λy=n(n+1)[a x^(n+1)+bx^(-n)]


λy=n(n+1)


λ=n(n+1)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

If y = 3 cos(log Mathematics - Board Papers

If x = t2</sMathematics - Exemplar

If x = a cos θ + Mathematics - Board Papers

If <iMathematics - Exemplar

If y =(tan–1Mathematics - Board Papers

If y = (tan Mathematics - Board Papers

Differentiate <spMathematics - Board Papers

Find<span lang="EMathematics - Board Papers

If y = xx</sMathematics - Board Papers

If x = a cos θ + Mathematics - Board Papers